Meta-Analysis of the Influence of Corporate Social Responsibility (CSR) on Profitability to Assess the Company's Financial Performance - Fitri Noviyanti; Shenia Meyrsa Rosanti; Hwihanus (Indonesian Journal of Entrepreneurship and Startups, 2024)
Corporate Social Responsibility (CSR) is the company's social responsibility to the surrounding environment. The condition of the company can be seen through the company's financial performance in generating profits every year. If profits continue to rise every year, the company's management has succeeded in carrying it out. However, if profits continue to decline or are unstable, the company management needs to evaluate and make strategies so that the profits generated by the company can increase. The main purpose of CSR activities is to obtain an increase in profit, because profit is very instrumental in maintaining the survival of the company in accordance with the principle of going concern. To achieve this, the company can improve its performance by managing its business activities effectively, efficiently, and economically. This article uses the meta-analysis method, namely by comparing several articles that have similar topics. The results show that more research shows that CSR (Corporate Social Responsibility) has a positive effect on the profitability generated by a company so that the financial performance of the company is getting better.